An African Alternative to Western Cosmological Argument Hopeless Reliance on Ontological Argument - Kiatezua Lubanzadio Luyaluka (Randwick International of Social Science Journal, 2020)
This paper demonstrates that as used in Western philosophy cosmological argument relies on ontological argument to jump to its conclusion about the existence of a Supreme-being-creator. Pointing to the failure of the Western cosmological argument, the paper shows that either creation happens within the creator or outside of him. In the first case, the Supreme-being-creator is not immutable; hence, he is not perfect. In the second case a greater being can be conceived which includes creator and creation. Therefore, the Western cosmological argument hopelessly relies on ontological argument to anticipate a priori that the first cause of its conclusion is God, the greatest possible being and a being of maximum perfection. As an alternative to this debunked cosmological argument, this paper offers the kemetic cosmological argument as a valid demonstration of the existence of a Supreme Being absolutely immutable and who is the greatest possible being